Adaptacja fonetyczna i graficzna anglicyzmów w rosyjskim slangu młodzieżowym - Kubecka, Katarzyna (Studia Rossica Posnaniensia, 2019)
The article analyses phonetic and graphic variations of majority of English borrowings in Russian youth slang, caused by the coexistence of two different methods of recording English borrowings with the letters of Russian alphabet. The findings of the analysis prove that the dominant way of transferring English borrowings into Russian slang corresponds with the slang’s tendency to show the russified version of English pronunciation in a written form.